The 2021-22 surge in inflation - Oleksiy Kryvtsov; James MacGee; Luis Uzeda (Bank of Canada, 2023)
The rise in inflation in 2021-22 sparked a growing literature and debate over the causes of the surge as well as the near- and medium-term path for inflation. This review offers three key messages. First, the exceptional nature of shocks resulting from the COVID-19 pandemic and geopolitical events drove the surge in inflation and the initial underestimation by many central banks of the extent of inflationary pressures. Second, the pandemic may have accelerated structural changes in goods and labour markets, which are likely to put pressure on goods prices and wages in the medium and long term. Third, the resulting shifts in relative prices for goods, services and labour are unlikely to be large enough to threaten a return of inflation to target but may require somewhat higher interest rates than those in the decade before the pandemic.
Keywords: E31; E52; E58; 330; Inflation and prices; Inflation targets; Monetary policy